2017
DOI: 10.1111/codi.13755
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of the role of metronidazole in post‐haemorrhoidectomy pain relief

Abstract: Metronidazole is a cheap, safe and effective intervention for reducing postoperative pain following conventional haemorrhoidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 28 publications
2
28
0
1
Order By: Relevance
“…We agree with Lyons et al .’s recent systematic review that concluded that metronidazole does reduce pain significantly following haemorrhoidectomy. Although they had similar methodology to ours, we disagree with the inclusion of one paper that included GTN with metronidazole in the intervention group as GTN has been shown to independently reduce pain .…”
Section: Resultssupporting
confidence: 91%
“…We agree with Lyons et al .’s recent systematic review that concluded that metronidazole does reduce pain significantly following haemorrhoidectomy. Although they had similar methodology to ours, we disagree with the inclusion of one paper that included GTN with metronidazole in the intervention group as GTN has been shown to independently reduce pain .…”
Section: Resultssupporting
confidence: 91%
“…The use of oral metronidazole in controlling postoperative pain was recently evaluated in two meta-analysis with conflicting results [186,187].…”
Section: Bleeding: Fewer People Have Postoperative Bleeding After Thdmentioning
confidence: 99%
“…There have been 3 systematic reviews [20][21][22] published in recent years assessing the analgesic effects of metronidazole in posthaemorrhoidectomy patients. While these reviews have pooled more patients, all 3 reviews included both open and closed haemorrhoidectomies, which is not generalizable to open haemorrhoidectomy alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, on subanalysis they did find lower reported pain scores on day 1 (standardised mean difference [SMD], -0.87 ± 0.44; 95% CI, -1.73 to -0.015; P = 0.046) and day 4 (SMD, -1.43 ± 0.71; 95% CI, -2.83 to -0.037; P = 0.044). The other 2 systematic reviews [21,22] reported a significant decrease in pain associated with metronidazole use. One review [21] performed a meta-analysis on days 1, 7, and 14; the other review [22] assessed pain on days 1, 2, and 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation